FINDING THE TRANSCENDENTAL BEAST IN POETIC TRANSLATIONS OF CHAIRIL ANWAR’S AKU - Nasrul Chotib, Mochamad; Subyanto, Arif; Masduqi, Harits; Widodo, Herditya Wahyu (E-Journal of Cultural Studies, 2023)
This study sets out to present the combined application of qualitative research and a translation method to elucidate the transcendental aspect of Chairil Anwar's poem entitled Aku. The translation process uses the poem’s verbatim format at first, then its interpretation of the content, and finally its inherent ideas by reading behind its lines. The transcending process is achieved through the use of a symbolic beast that permeates the poem’s structure. The beast-symbol has twofold functions in the poem, to say that everything beyond the persona-self is unworthy and thus the persona itself is capable of reaching a more divine place or becoming a higher being. Such a powerful symbol further substantiates the presence of a textual being, a voice of a persona that is inherent within the poem’s structure, and of which function is to express the persona’s wish to transcend into something bigger or higher than himself, which is resembling, if not equal to, a godly being. Keywords: poem’s persona, poetic translation, transcendentalism.